Analisis Beban Kerja di Laboratorium ProduksiPT. XYZ Dengan Metode CVL dan NASA-TLX - Adi Cahyono Putra; Akhmad Wasiur Rizqi; Moh. Jufriyanto (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
To evaluate the workload, one can consider the combination of physical and mental effort that employees undergo. The quantification of physical workload is accomplished through the utilization of the Cardiovascular Load (%CVL) methodology, whereas the evaluation of mental workload is conducted employing the NASA-TLX methodology.Pulse measurement is employed to gather data on the physical exertion level. Concurrently, the cognitive load was alleviated by administering NASA-TLX surveys to the personnel. Thephysical workload measurements were acquired from a sample of 12 employees who showed no indications of fatigue. Meanwhile, the measurements of mental workload indicate a substantial level of both elevated and extremely elevated workload One employee was classified as having an extremely heavy workload, while the majority of respondents (11 out of 12) assessed their workload as high. The results suggest that around 33% of employees face a substantial mental workload, underscoring the need for a leadership policy focused on workload reduction